1980
DOI: 10.1104/pp.65.3.483
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ultraviolet-B Irradiances on Soybean

Abstract: Soybean plants (cv. Hardee) were grown from seed under four ultraviolet-B radiation flux densities and four photosynthetically active radiation levels in a factorial design. Net photosynthesis, dark respiration, and transpiration were measured after 2 and 6 weeks of exposure. Effects of ultraviolet-B radiation were dependent upon photosynthetically active radiation levels. Ultraviolet-B radiation adversely affected net photosynthesis at low photosynthetically active radiation levels, but had little consequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(24 citation statements)
references
References 16 publications
3
21
0
Order By: Relevance
“…2) that occurred support the hypothesis that existing ambient UV-B radiation levels inhibit certain physiological processes as previously suggested by Sisson and Caldwell (17) and Teramura et a. (18). The UV-BBE impinging upon the leaf surface of the plants used in this experiment would probably be higher than that impinging on leaves in a field situation for equivalent ambient UV-BBE since the first leaves were held at normal incidence to the UV-B radiation sources and were not shaded by later leaves.…”
Section: Methodssupporting
confidence: 85%
“…2) that occurred support the hypothesis that existing ambient UV-B radiation levels inhibit certain physiological processes as previously suggested by Sisson and Caldwell (17) and Teramura et a. (18). The UV-BBE impinging upon the leaf surface of the plants used in this experiment would probably be higher than that impinging on leaves in a field situation for equivalent ambient UV-BBE since the first leaves were held at normal incidence to the UV-B radiation sources and were not shaded by later leaves.…”
Section: Methodssupporting
confidence: 85%
“…Only a few studies have employed UV-B doses equivalent to less than a 20% reduction in the ozone layer. Nevertheless, these studies have also demonstrated the deleterious effects of UV-B irradiation upon plants (24)(25)(26)(27).…”
Section: Abstracimentioning
confidence: 99%
“…Caldwell (7) estimated that a 1% decrease in stratospheric ozone concentration would result in an approximate 2% increase in UV-BBE2 radiation at temperate latitudes. Therefore, the recently projected 5 to 9% stratospheric ozone reduction (18) would result in up to a 19% increase in UV-BBE radiation.An increase in UV-B irradiance is of particular concern since energy in this waveband is readily absorbed by proteins and it has been demonstrated that plant processes such as photosynthesis (25), transpiration (7, 25), leaf expansion (10, 23, 26, 27), dark respiration (22,25), and biomass allocation (24) are affected. In the majority of UV-B studies, the UV-B dose utilized was 3-to 5-fold greater than the National Academy of Science's most recent estimates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of increased UV-B are particularly marked at low intensities of visible light (Teramura et aL, 1980). While UV-B wavelengths are not used directly for photosynthesis, they can afect the process indirectly by altering enzyme effciency, chlorophyll pigment structure (and hence light-gathering capacity) and lipid and carbohydrate pools (Berenbaum, 1988).…”
Section: Uv-b Effects On Plants; Herbivores and Phytopathogensmentioning
confidence: 99%